Efficacy of intraoperative cine‐portogram for complicated portal vein reconstruction in pediatric living donor liver transplantation. (4th September 2020) - Uchida, Hajime; Sakamoto, Seisuke; Shimizu, Seiichi; Takeda, Masahiro; Yanagi, Yusuke; Fukuda, Akinari; Abdelwahed, Mohamed Sami; Miyazaki, Osamu; Nosaka, Shunsuke; Kasahara, Mureo
Abstract: Sufficient PV flow is necessary to achieve successful PV reconstruction in pediatric LDLT. IOCP can be used to assess the severity of PV stenosis and to identify potential portosystemic collateral pathways. The present study reviewed the utility of IOCP and the outcomes of patients who underwent assessment with an IOCP. Consecutive primary LDLTs were performed in 488 pediatric recipients between November 2005 and October 2019. IOCP was used in patients who were unable to achieve sufficient PV flow after the ligation of collaterals. In total, 11 patients underwent IOCP to assess potential portosystemic collateral pathways. The median age and body weight was 8 months (IQR, 6‐11 months) and 6.6 kg (IQR, 5.7‐8.9 kg), respectively. The reasons for using the IOCP were recurrent PV thrombus in seven patients and insufficient PV flow in four patients. IOCP revealed remaining collaterals in six patients and residual hypoplastic PV in eight patients. Two patients required additional interruption of the potential collaterals under IOCP, which were unable to be recognized as a dominant portosystemic collateral pathway on preoperative imaging. All eight patients with residual hypoplastic PV required vein graft interposition for the complete removal of the hypoplastic PV. All the patients are currently doing well with a median follow‐up period of 4.9 years (IQR, 2.2‐5.6 years). IOCP can be an effective tool for precisely detecting occult portosystemic collateral pathways and for assessing the patency of the PV anastomosis in pediatric LDLT.